How has the nation been coping? A corpus analysis of Malaysian letters to the editor in another COVID-19 community-wide containment - Siti Aeisha Joharry; Syamimi Turiman; Maisarah Ahmad Kamil (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the development of the COVID-19 pandemic, we have seen a rise in digitalisation that includes receiving and/or reading information online. There is a wealth of citizen journalism such as letters to editors that are garnering wider readability based on availability of news offered online as well as netizens’ independence to search for more credible sources on the web. The present study aims to examine a corpus of Malaysian online letters to editors that reflect public expressions of the second community-wide containment, also known as the Movement Control Order (MCO2.0) in the country. Following the corpus linguistics approach, frequency word lists are firstly extracted from public online letters in a popular national newspaper, which are further investigated in terms of collocational analysis and close inspection of words and phrases that are used in context via concordancing. This analysis is comparable to highlighting any similarities or differences expressed among Malaysians in a previous study conducted during the first MCO. Findings showed that letters during MCO2.0 were more about COVID-19 vaccines compared to the crisis and restricted movements in the first MCO. In-depth speech acts analysis, according to Searle (1979), revealed that discussions related to vaccination are mostly in favour of the government’s plan in making vaccines free and accessible regardless of citizenship.